Occurrence of Fungi on Duck Egg Shells and Drug Resistance Analysis of Aspergillus spp. Isolates - Andrzej Gaweł; Magdalena Siedlecka; Magdalena Karwańska; Milena Skrok; Iwona Przychodniak; Piotr Knap; Aleksandra Chmielina; Violetta Truszko; Maciej Kuczkowski; Karolina Bierowiec; Anna Woźniak-Biel; Barbara Szczepankiewicz; et al. (Applied Sciences)
Fungi are a typical part of the microbiome of poultry houses, but some of the genera can be pathogenic for poultry and humans. An investigation was conducted on 200 duck eggs from 10 flocks to determine total fungal contamination on the eggshells. The colony types were identified morphologically and microscopically, and a representative group was identified using PCR. The resistance profiles for all obtained Aspergillus isolates were conducted. The dominating genera on eggshells were Penicillium, Alternaria and Aspergillus and the number of fungal colonies ranged from 0 to 7100. Aspergillus fumigatus was cultured from 9.5% eggshells, and all isolates were obtained from three flocks. The minimum inhibitory concentration (MIC) values for A. fumigatus isolates ranged from 0.094–32 μg/mL for amphotericin B (MIC 50 1 mg/L and MIC 90 32 μg/mL), 0.125–32 μg/mL for caspofungin (MIC 50 0.38 μg/mL and MIC 90 32 μg/mL), 0.19–32 μg/mL for itraconazole (MIC 50 1.5 μg/mL and MIC 90 32 μg/mL), 0.047–12 μg/mL for posaconazole (MIC 50 0.5 μg/mL and MIC 90 8 μg/mL) and 0.023–32 μg/mL for voriconazole (MIC 50 0.19 μg/mL and MIC 90 32 μg/mL). A total of 73.7% of the isolates were resistant to posaconazole and 68.4% to itraconazole. Nearly half of the strains (47.4%) showed resistance to amphotericin B and 31.6% to voriconazole. Because of the lack of antifungals registered for poultry, hygiene and the regular disinfection of litter in particular are needed to prevent the contamination of the eggs by fungi for both animal and human health.